ISSUES REGARDING THE FINANCIAL FLOW PROJECTIONS IN THE SELECTION OF INVESTMENT PROJECTS - Mariana Rodica ŢÎRLEA (SEA: Practical Application of Science, 2015)

(untitled)
For a company, through investment activities, it is followed to either create new abilities or expand the existing abilities, the partial or complete replacement of existing technical base or its modernization. In the condition that it is desired the creation of a technical base, the investment involves the purchase of fixed capital that can materialize in: buildings, special buildings, land, vehicles, facilities, equipment, etc. In terms of expansion and modernization, investment implies the existence of a material base on which should be intervened wholly or partly by its development or modernization. For the selection of investment projects in the context of investment strategy established at enterprise level through a Financial justification and prioritization of investments this should lead to the achievement of the objectives set at its level.